Evening Gun, no. 251, in E.C. Wharton, New Orleans Laws and General Ordinances 89 (1857). - (:unkn) unknown (My University, 1857)
That the captains of police of the first, second, third and fourth districts be, and are hereby, instructed to purchase the powder necessary for firing the evening guns in said districts, and present the vouchers for the same, after they have been approved by the chief of police, and it shall be the duty of the said captains to detail a member of the police force of each of said districts to fire the said evening guns, without extra compensation."
Keywords: PEACE OFFICERS